Kajian Terhadap Akuntansi Sumber Daya Manusia Untuk Meningkatkan Kualitas Informasi Keuangan (Studi pada PT. Multi Agro Chemical Industry, Terbanggi Besar, Lampung Tengah) - Yogi Akbar S (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
The calculation of the velocity ratio of investment (ROI) when using conventional accounting on PT.Multi Agro Chemical Industry, Terbanggi Large, Central Lampung has many limitations, because it istoo focused on short-term results and ignore employee relations, cost, employee development, and alot of spending on human resource development is not counted in the investment even the outcomehas given outcome contribution in the future.In 2004, based on conventional accounting showed the ability of companies to make profits with theassets owned by 45.352% and ROI calculation based on the ASDM by 45.977%. By using ASDM ROIcalculation increased by 0.0927%, but not so well in 2004, accounting for the ratio by using ASDMfor the better.